Pengembangan Model Aplikasi Pelatihan Pengendalian Mutu Computed Tomography (CT) Berbasis American College of Radiology (ACR) Phantom Terintegrasi Web - Harnanto, Rudy; Adi, Kusworo; Dartini, Dartini; Wibowo, Gatot Murti; Rasyid, Rasyid (Poltekkes Kemenkes Semarang, 2025)
Background: The use of Viewdex as a tool for radiographic image evaluation has limitations in flexibility for students, particularly in the installation and input of DICOM ACR image results, which can be complex. This study aims to: (1) Evaluate the performance of the CT Scan training application for the Applied Bachelor Program in Radiologic Imaging Technology at Poltekkes Kemenkes Semarang, based on ViewDex; (2) Develop a web-integrated CT Scan quality control training application based on the ACR Phantom; (3) Measure the performance of the web-integrated CT Scan quality control training application based on the ACR Phantom.Methods: The research method used is Research and Development (RD), which includes literature study, product development, field testing, evaluation, and product revision. The developed application simplifies the process of importing DICOM data, coding questions, and automatic evaluation, thus improving operational efficiency.Results: Validation by IT and QA/QC experts shows that the application meets high standards with 100% validity. Blackbox testing, which includes general functionality, security, compatibility, performance, usability, dashboard, and user interface, showed that the application is valid and operates well without significant errors. Performance evaluation through pre-test and post-test indicated a significant improvement in participants' knowledge and skills, with the Wilcoxon test yielding a p-value of 0.005, indicating a significant difference between conditions before and after using the application.Conclusions: in conclusion, the developed application is effective and efficient in enhancing student usability and learning experience, overcoming the limitations of Viewdex. This application enables efficient management and analysis of medical images and data, making it well-prepared to support CT quality control training with high-quality standards.